New electroanalytical method for the determination of trans-anethole in spices and sweets - Jashari, Granit; Frühbauerová, Michaela; Mikysek, Tomáš; Švancara, Ivan; Metelka, Radovan; Sýs, Milan (Elsevier Science, 2023)
A completely new method for the determination of trans-anethole (TAN) based on the anodic oxidation of this flavouring substance in pure acetonitrile using differential-pulse voltammetry has been developed. A nonaqueous carbon paste electrode bulk-modified with solid sodium dodecyl sulphate of 40 % (w/w) content was chosen as optimum. To propose TAN electrode reaction mechanism, its electrochemical behaviour was inves-tigated at glassy carbon electrode in nonaqueous media. At optimum working conditions, the current response could be calibrated within a linear range 2-200 μmol L−1 TAN, a coefficient of determination of 0.9971, a sensitivity of 0.1122 μA L μmol−1 and a detection limit of 0.7 μmol L−1. A satisfactory precision (relative stan-dard deviation of 4 %) has been achieved. The validation performed by analysis of spices and sweets provided comparable results with reference reverse-phase HPLC with spectrophotometric detection, thus confirming the practical use of the developed voltammetric method in food analysis.
Nová elektroanalytická metoda pro stanovení trans-anetholu v koření a sladkostech
Keywords: Trans-anethole; nonaqueous carbon paste electrode; differential pulse voltammetry; additive analysis; Trans-anethol; nevodná uhlíková pastová elektroda; diferenční pulzní voltametrie; aditivní analýza